High malaria parasitemia in an Italian man and severe delayed hemolytic anemia - Massimiliano Lanzafame; Giovanni Mori; Emanuela Lattuada; Claudio Scarparo (Clinical Case Reports)
Key Clinical Message Parenteral artesunate has become the choice treatment of cases of high parasitemia malaria. We report the case of an Italian man with a high malaria parasitemia who promptly improved with intravenous artenusate, but who developed a delayed severe hemolytic anemia associated with intravenous artesunate treatment, requiring blood trasfusions.